A review on graph search algorithms for optimal energy efficient path planning for an unmanned air vehicle - Sanjoy Kumar Debnath; Rosli Omar; Nor Badariyah Abdul Latip; Shasha Shely; Elia Nadira; Che Ku Nor Che Ku Melor; Tapan Kumar Chakraborty; Elango Natarajan (Institute of Advanced Engineering and Science, 2019)
Unmanned Air Vehicle (UAV) has attracted attention in recent years in conducting missions for longer time with higher levels of autonomy. For the enhanced autonomous characteristic of UAV, path planning is one of the crucial issues. Current researches on the graph search algorithms under combinatorial method are mainly reviewed in this paper by keeping focus on the comprehensive surveys of its properties for path planning. The outcome is a pen picture of their assumptions and drawbacks.